Unlocking the potential: FKK6 as a microbial mimicry-based therapy for chronic inflammation-associated colorectal cancer in a murine model - Sládeková, Lucia; Li, Hao; DesMarais, Vera M; Beck, Amanda P; Guzik, Hillary; Vyhlídalová, Barbora; Gu, Haiwei; Mani, Sridhar; Dvořák, Zdenek (The Journal of pharmacology and experimental therapeutics, 2025)
Chronic intestinal inflammation significantly contributes to the development of colorectal cancer and remains a pertinent clinical challenge, necessitating novel therapeutic approaches. Indole-based microbial metabolite mimics Felix Kopp Kortagere 6 (FKK6), which is a ligand and agonist of the pregnane X receptor (PXR), was recently demonstrated to have PXR-dependent anti-inflammatory and protective effects in a mouse model of dextran sodium sulfate (DSS)-induced acute colitis. Here, we examined the therapeutic potential of FKK6 in a mouse model (C57BL/6 FVB humanized PXR mice) of colitis-associated colon cancer (CAC) induced by azoxymethane and DSS. FKK6 (2 mg/kg) displayed substantial antitumor activity, as revealed by reduced size and number of colon tumors, improved colon histopathology, and decreased expression of tumor markers (c-MYC, β-catenin, Ki-67, and cyclin D) in the colon. In addition, we carried out a chronic toxicity (30 days) assessment of FKK6 (1 mg/kg and 2 mg/kg) in C57BL/6 mice. Histological examination of tissues, biochemical blood analyses, and immunohistochemical staining for Ki-67 and γ-H2AX showed no difference between FKK6-treated and control mice. Comparative metabolomic analyses in mice exposed for 5 days to DSS and administered with FKK6 (0.4 mg/kg) revealed no significant effects on several classes of metabolites in the mouse fecal metabolome. Ames and micronucleus tests showed no genotoxic and mutagenic potential of FKK6 in vitro. In conclusion, anticancer effects of FKK6 in azoxymethane/DSS-induced CAC, together with FKK6 safety data from in vitro tests and in vivo chronic toxicity study, and comparative metabolomic study, are supportive of the potential therapeutic use of FKK6 in the treatment of CAC. SIGNIFICANCE STATEMENT: Microbial metabolite mimicry proposes that chemical mimics of microbial metabolites that serve to protect hosts against aberrant inflammation in the gut could serve as a new paradigm for the development of drugs targeting inflammatory bowel disease if, like the parent metabolite, is devoid of toxicity but more potent against the microbial metabolite receptor. We identified a chemical mimic of Felix Kopp Kortagere 6, and we propose that Felix Kopp Kortagere 6 is devoid of toxicity yet significantly reduces tumor formation in an azoxymethane-dextran sodium sulfate model of murine colitis-induced colon cancer.
Keywords: molekulární mimikry; indoly; Indoles; Chronic Disease; Dextran Sulfate; Female; Inflammation; Colitis-Associated Neoplasms; zvířata; myši; azoxymethan; zánět; myši inbrední C57BL; Azoxymethane; Mice; síran dextranu; ženské pohlaví; kolorektální nádory; Male; chronická nemoc; Mice, Inbred C57BL; kolitida; nádory asociované s kolitidou; Animals; mužské pohlaví; Disease Models, Animal; Colitis; Colorectal Neoplasms; modely nemocí na zvířatech; Molecular Mimicry